STUDI KUALITAS AIR TANAH DANGKAL DAN PENDAPAT MASYARAKAT SEKITAR TEMPAT PEMROSESAN AKHIR SAMPAH SUWUNG KECAMATAN DENPASAR SELATAN, KOTA DENPASAR - Eka Subrata Jaya, I. W. Agus; Suarna, I Wayan; Redi Aryanta, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 10 No 1 (2016), 2016)
Research has been conducted to determine the quality of shallow groundwater (dug-wells and shallow bore-wells) and the local communities opinions around the landfill Suwung. The method of determining the station was done by purposive sampling, where the station sampling was determined by selecting a place which was expected to represent the whole area.Water sampling of dug-wells was conducted by using a water sampler and the shallow bore-wells using a 2-liter bottle. Data was analyzed by descriptive comparative referenceto class I water quality of the Bali Governor Regulation No.8 of 2007. The public opinion data was obtained by using aquesioner filled by respondents who have and use wells and shallow bore wells for their daily needsand it was analyzed by using frequency distribution tables.The results showed that the quality of shallow groundwater (dug-wells and shallow bore-wells) did not meet water quality standards in accordance with the rules of the class defined in the Governor of Bali Regulation No. 8 of 2007. The water pollution index (PI) of dug-wells at a distance of 1-400 meters was in hearily polluted category, while water fromshallow bore-wells drilled at a distance of 1-200 meters was in the category of hearily polluted and at a distance of 201-400 meters was in the category of medium polluted.There was an increasing range of groundwater quality deterioration in 1997, 2008 and 2014. In 1997, contaminated shallow groundwater has occured at a distance of 80 meters, while in 2008, the pollution has occurred up to a distance of 375 meters and in the year of 2014 the contamination occurred from a distance of 1 meter to 400 meters. The average of score Pollution Index (PI) of Water wells in the year of 2008 amounted to 14.55, while in 2014 up to 15.44. It is estimated that the water quality of dug-wells and bore-wells will meet the quality standards in accordance with the value of the pollution index at a distance of over 5000 meters and 750 meters of the Suwung landfill waste.Most of the respondents who live in the vicinity Suwung landfill waste tend to give an opinion that the shallow groundwater (dug-wells and shallow bore-wells) has decreased quality as drinking water. Approximately 75% of respondents thought that the well water in their environment has been reduced in quality.
Keywords: Shallow groundwater; landfill waste of Suwung; pollution index; groundwater quality